Theory of Common Education in Elizabethan Puritanism - Short, K. R. M. (The journal of ecclesiastical history, 1972)
Professor L. A. Stone, writing on the ‘educational revolution’ of the period 1560–1640, came to the conclusion that one of the ‘most striking characteristics of the English Puritans was their belief in the value of education as a weapon against the three great evils of Ignorance, Prophaneness and Idleness’. He found that a significant number of puritan gentry and merchants supported the ‘teaching of the three R's and religion to the many, and Latin and religion to the few’ through the many scholarships and foundations that appear in this period. One may, however, question Stone's contention that the Puritans' educational motives were tied to the inculcation of obedience to the established social and political order. It is more than likely that, by spreading the Word of God, defeating what he calls the aesthetic and emotional attractions of the counter-reformation, and establishing a truly protestant nation, Puritans sought to educate a breed of reformed men dedicated to the coming of the Kingdom of God in their own lifetime. This, conceivably, was what was meant by a genuinely learned and protestant society.